2014
DOI: 10.1186/1471-2202-15-104
|View full text |Cite
|
Sign up to set email alerts
|

Power spectral aspects of the default mode network in schizophrenia: an MEG study

Abstract: BackgroundSymptoms of schizophrenia are related to deficits in self-monitoring function, which may be a consequence of irregularity in aspects of the default mode network (DMN). Schizophrenia can also be characterized by a functional abnormality of the brain activity that is reflected in the resting state. Oscillatory analysis provides an important understanding of resting brain activity. However, conventional methods using electroencephalography are restricted because of low spatial resolution, despite their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 76 publications
(90 reference statements)
3
56
0
Order By: Relevance
“…In our prior studies, we have found that resting state networks in ASD, ages 8–18, showed increased efficiency in the gamma band, but decreased efficiency in the beta band (Kitzbichler et al, 2015). In parallel, studies have shown reduced efficiency in the alpha band in bipolar disorder and schizophrenia (Hinkley et al, 2011; Kim et al, 2013, 2014), and abnormal resting state network connectivity in the gamma band (Andreou et al, 2015). The observation of resilience, a measure that depends on network efficiency, increased with age in the beta band but decreased with age in the gamma band, diverges from our original hypothesis of minimal resilience during adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…In our prior studies, we have found that resting state networks in ASD, ages 8–18, showed increased efficiency in the gamma band, but decreased efficiency in the beta band (Kitzbichler et al, 2015). In parallel, studies have shown reduced efficiency in the alpha band in bipolar disorder and schizophrenia (Hinkley et al, 2011; Kim et al, 2013, 2014), and abnormal resting state network connectivity in the gamma band (Andreou et al, 2015). The observation of resilience, a measure that depends on network efficiency, increased with age in the beta band but decreased with age in the gamma band, diverges from our original hypothesis of minimal resilience during adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…The same conceptualization has been applied to the resting EEG, particularly in the context of psychopathology (Kim et al, 2014; Pizzagalli, 2011). It should be recognized that the distinction between net and overall alpha cannot be made in EEG studies in which only eyes-closed resting alpha is recorded.…”
Section: Discussionmentioning
confidence: 99%
“…However, the implications of a resting alpha blockade and alpha ERD are considerably different: while the former is a measure of arousal from relaxation, the latter may be viewed as an index of top-down processes associated with attention (von Stein, Chiang, König, 2000; Kayser et al, 2014). A related conceptualization is the default mode network (DMN), which has also been associated with resting activity related to EEG alpha and theta (Farber et al, 2014; Kim et al, 2014; Pizzagalli, 2011; Qin et al, 2010). Despite these overlapping processes, it is unclear whether resting- and task-related EEG alpha provide comparable or complementary information.…”
Section: Introductionmentioning
confidence: 99%
“…Two more recent MEG studies by [29,5], have shown that neuronal patterns in the default mode network (DMN) during rest can be used to identify patients with schizophrenia compared to controls [29] used MEG to identify the DMN regions and found that the spatial distribution of DMN activity in the alpha band was similar to that found in previous fMRI studies [29]. The DMN and resting activities of the posterior cingulate cortex (PCC) were increased in schizophrenia patients, predominantly in the theta and alpha bands.…”
mentioning
confidence: 98%